A review of factors affecting traceability in agrifood supply chain. (31st December 2009) - Manikas, Ioannis; Manos, Basil
The efficiency of a traceability system lies on the ability to collect information related to product quality and consumer safety. There is a wide range of traceability systems currently used in food chains; from paper-based to IT enabled. In this paper, the different approaches given in literature on the requirements of a successful traceability support system are reviewed, and the factors that influence the effectiveness of traceability in the agrifood sector are identified. Moreover, the objectives of such system were determined as well as its individual operations, the needs and the attitude of agrifood industry toward such systems.